Parents’ Role in Supporting, Brokering or Impeding Their Children’s Connected Learning and Media Literacy - Livingstone Sonia; Blum-Ross Alicia (Cultural Science)
How do parents and carers approach the task of bringing up their children in the digital age? What is their vision of their children’s future and that of the wider society? Most importantly, how are parental expectations, and expectations of parents, designed into learning opportunities for children, if at all? In this article, our focus is on how children gain media literacy in a range of non-formal sites including after school clubs, digital media learning courses, makerspaces and, of course, the home.